Effects of cooking methods on antioxidant properties, quality attributes, and sensory characteristics of selected leafy greens - St. Onge, Matthew Mark, author; Bunning, Marisa, advisor; Stone, Martha, advisor; Newman, Steven, committee member (Colorado State University. Libraries, 2014)
Kale, arugula, spinach, and other types of leafy vegetables are rich sources of vitamins and minerals and well-suited to growing in Colorado's climate. This project focused on the chemical, quality, and sensory assessment of a selection of 6 specialty leafy greens (arugula, cherokee lettuce, mache, pac choi, red kale, and spinach). Total phenolic (TP) content, radical scavenging capacity (1,1-diphenyl-2-picrylhydrazyl, DPPH), color measurement, instrumental texture characteristics, and sensory attributes of raw versus cooked (boiled, microwaved, or steamed) samples of the select taxa were analyzed and evaluated. All 6 varieties were cultivated in a greenhouse using organic planting medium. Samples of the greens were freeze-dried as raw or post-heat treatment, then underwent an extraction procedure, and were analyzed for total phenolics compared to gallic acid standards and radical scavenging using DPPH compared to trolox standards. Fresh and cooked comparisons were tested for color differences using a HunterLab ColorFlex spectrophotometer and changes in texture utilizing a TA-XT2 texture analyzer. Consumer (n=50; n=51) sensory analysis was administered using a 9-point hedonic scale. Fresh, uncooked mache had higher (p<0.05) total phenolics and radical scavenging ability than all other cultivars. Cooked samples revealed that spinach values for each test did not differ (p>0.05) from fresh samples and microwaved and steamed samples of red kale contained more total phenolics than fresh, but less (p<0.05) was observed in boiled samples. Other significant findings included reductions (p<0.05) in lightness of cooked samples and cooked spinach samples after all heating treatments were observed to be more tender than fresh samples (p<0.05). This research helps to fill information gaps which exist in leafy greens research. Many studies focus on one cultivar using one testing method, but little research has been conducted on these types of greens using several analytical testing methods to obtain comparable data.
Keywords: DPPH; cooked greens; leafy greens; mache; red kale; texture analysis